2016
DOI: 10.1038/ncomms13314
|View full text |Cite
|
Sign up to set email alerts
|

How EF-Tu can contribute to efficient proofreading of aa-tRNA by the ribosome

Abstract: It has long been recognized that the thermodynamics of mRNA–tRNA base pairing is insufficient to explain the high fidelity and efficiency of aminoacyl-tRNA (aa-tRNA) selection by the ribosome. To rationalize this apparent inconsistency, Hopfield proposed that the ribosome may improve accuracy by utilizing a multi-step kinetic proofreading mechanism. While biochemical, structural and single-molecule studies have provided a detailed characterization of aa-tRNA selection, there is a limited understanding of how t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
113
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(130 citation statements)
references
References 70 publications
14
113
1
Order By: Relevance
“…This is central to the fidelity of gene expression, where the overall accuracy depends sensitively on accommodation kinetics . In addition, previous simulations have shown that a static EF‐Tu molecule can confine aa‐tRNA motion and reduce the free‐energy barrier of accommodation . Here, we consider whether a dynamic, extended and disordered EF‐Tu molecule could also influence accommodation kinetics.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is central to the fidelity of gene expression, where the overall accuracy depends sensitively on accommodation kinetics . In addition, previous simulations have shown that a static EF‐Tu molecule can confine aa‐tRNA motion and reduce the free‐energy barrier of accommodation . Here, we consider whether a dynamic, extended and disordered EF‐Tu molecule could also influence accommodation kinetics.…”
Section: Resultsmentioning
confidence: 99%
“…For example, kinetic and single‐molecule measurements have shown that EF‐Tu can undergo a conformational change before dissociating from the ribosome, and other single‐molecule FRET measurements suggest aa‐tRNA can sample partially‐accommodated configurations prior to EF‐Tu dissociation. With regards to theoretical analyses, simulations have shown that EF‐Tu may confine aa‐tRNA movement, which has the potential to modulate the free‐energy barrier for aa‐tRNA accommodation . Here, we aim to further characterize the relationship between EF‐Tu and aa‐tRNA dynamics by quantifying the accessibility of extended/disordered ensembles when EF‐Tu is partially associated with the ribosome.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For a definitive result, two ribosomal attributes stand out for investigation because they relate directly to ribosome activity, though can still be influenced by trans-factors [71]. These are the elongation and error rates of the ribosome (Figure 5C, 5D).…”
Section: Identifying Ribosome Heterogeneitymentioning
confidence: 99%
“…mRNA specificity represents a key area where ribosome specialization could play a role ( Figure 5B). However, the degree of association of an individual mRNA with specific ribosomes can be determined not only by increased affinity of specialized ribosomes for the mRNA but also by altered mRNA abundance, and translation initiation factors.For a definitive result, two ribosomal attributes stand out for investigation because they relate directly to ribosome activity, though can still be influenced by trans-factors [71]. These are the elongation and error rates of the ribosome (Figure 5C, 5D).…”
mentioning
confidence: 99%